Arsenic tolerant Trichoderma sp. reduces arsenic induced stress in chickpea (Cicer arietinum). (April 2017) - Tripathi, Pratibha; Singh, Poonam C.; Mishra, Aradhana; Srivastava, Suchi; Chauhan, Reshu; Awasthi, Surabhi; Mishra, Seema; Dwivedi, Sanjay; Tripathi, Preeti; Kalra, Alok; Tripathi, Rudra D.; Nautiyal, Chandra S.
Abstract: Toxic metalloids including arsenic (As) can neither be eliminated nor destroyed from environment; however, they can be converted from toxic to less/non-toxic forms. The form of As species and their concentration determines its toxicity in plants. Therefore, the microbe mediated biotransformation of As is crucial for its plant uptake and toxicity. In the present study the role of As tolerant Trichoderma in modulating As toxicity in chickpea plants was explored. Chickpea plants grown in arsenate spiked soil under green house conditions were inoculated with two plant growth promoting Trichoderma strains, M-35 (As tolerant) and PPLF-28 (As sensitive). Total As concentration in chickpea tissue was comparable in both the Trichoderma treatments, however, differences in levels of organic and inorganic As (iAs) species were observed. The shift in iAs to organic As species ratio in tolerant Trichoderma treatment correlated with enhanced plant growth and nutrient content. Arsenic stress amelioration in tolerant Trichoderma treatment was also evident through rhizospheric microbial community and anatomical studies of the stem morphology. Down regulation of abiotic stress responsive genes (MIPS, PGIP, CGG) in tolerant Trichoderma + As treatment as compared to As alone and sensitive Trichoderma + As treatment also revealed that tolerant strain enhanced the plant's potential to cope with As stress as compared to sensitive one. Considering the bioremediation and plant growth promotion potential, the tolerant Trichoderma may appear promising for its utilization in As affected fields for enhancing agricultural productivity. Graphical abstract: Highlights: Trichoderma ameliorates As induced stress in chickpea. Trichoderma modulates stress responsive genes in presence of As in chickpea. Trichoderma inoculation methylates iAs into organic species in chickpea seeds. Trichoderma restores As induced anatomical deformities in chickpea. Abstract : Arsenic tolerant Trichoderma reduces arsenic toxicity in chickpea grown in arsenic spiked soil.